BRCA2 reversion mutation–independent resistance to PARP inhibition through impaired DNA prereplication complex function - Kyrie Pappas; Matteo Ferrari; Perianne Smith; Subhiksha Nandakumar; Zahra Khan; Serina B. Young; Justin LaClair; Marco Vincenzo Russo; Emmet Huang-Hobbs; Nikolaus Schultz; Wassim Abida; Wouter Karthaus; et al. (Proceedings of the National Academy of Sciences, 2025)
Recent approvals of polymeric adenosine diphosphate ribose (poly(ADP-ribose) polymerase inhibitors (PARPi) for BRCA-mutant metastatic castration resistant prostate cancer necessitate an understanding of the factors that shape sensitivity and resistance. Reversion mutations that restore homologous recombination (HR) repair are detected in ~50 to 80% of BRCA-mutant patients who respond but subsequently relapse, but there is currently little insight into why only ~50% of BRCA-mutant patients display upfront resistance. To address this question, we performed a genome-wide CRISPR screen to identify genomic determinants of PARPi resistance in murine Brca2 Δ/Δ prostate organoids genetically engineered in a manner that precludes the development of reversion mutations. Remarkably, we recovered multiple independent single guide RNAs (sgRNAs) targeting three different members ( Cdt1, Cdc6, and Dbf4 ) of the DNA prereplication complex (pre-RC), each of which independently conferred resistance to olaparib and the next-generation PARP-1 selective inhibitor AZD5305. Moreover, sensitivity to PARP inhibition was restored in Brca2 Δ/Δ , Cdc6-depleted prostate cells by knockdown of geminin, a negative regulator of Cdt1, further implicating the critical role of a functional pre-RC complex in PARPi sensitivity. Furthermore, ~50% of CRPC tumors have copy number loss of pre-RC complex genes, particularly CDT1 . Mechanistically, prostate cells with impaired pre-RC activity displayed rapid resolution of olaparib-induced DNA damage as well as protection from replication fork degradation caused by Brca2 loss, providing insight into how Brca2-mutant cancer cells can escape cell death from replication stress induced by PARP inhibition in the absence of HR repair. Of note, a pharmacologic inhibitor that targets the CDT1/geminin complex (AF615) restored sensitivity to AZD5305, providing a potential translational avenue to enhance sensitivity to PARP inhibition.